A phenotypic and mechanistic perspective on heterogeneity of HER2-positive breast cancers. (1st November 2016) - Ferrari, Anthony; Sertier, Anne-Sophie; Vincent-Salomon, Anne; Pivot, Xavier; Pauporté, Iris; Saintigny, Pierre; Birnbaum, Daniel; Viari, Alain
ABSTRACT: Analysis of gene expression and whole-genome features of 64 human epidermal growth factor 2 ( HER2 )-positive breast tumors supports the idea that their intrinsic heterogeneity actually reflects their cell of origin, suggesting that HER2 amplification is an embedded event in the natural history of these tumors. Possible mechanisms for this event involve breakage-fusion-bridge and chromothripsis.